Drugged : the Science and Culture Behind Psychotropic Drugs. - Miller, Richard J. (Oxford University Press, USA, 2013)
""Morphine, "" writes Richard J. Miller, ""is the most significant chemical substance mankind has ever encountered."" So ancient that remains of poppies have been found in Neolithic tombs, it is the most effective drug ever discovered for treating pain. ""Whatever advances are made in medicine, "" Miller adds, ""nothing could really be more important than that."" And yet, when it comes to mind-altering substances, morphine is only a cc or two in a vast river that flows through human civilization, ranging LSD to a morning cup of tea. In DRUGGED, Miller takes readers on an eye-opening tour of psyc.